Performance changes in National Collegiate Athletic Association Division I women basketball players during a competitive season: Starters Vs. nonstarters - Gonzales, A. M.; Hoffmann, J. R.; Scallin-Perez, J. R.; Stout, J. R.; Fragala, M. S. (The Journal of Strength and Conditioning Research, 2012)
The effects of playing time on performance changes were examined in National Collegiate Athletic Association Division I women basketball players. Twelve basketball players (age = 20.6 ± 1.5 years; height = 178.0 ± 8.2 cm; weight = 74.1 ± 8.1 kg) were assessed before (PRE) and at the end of the regular basketball season (POST). Assessments included squat power; vertical jump (VJ) power; 20-second lower-body reaction test; 3 line drills; and subjective measures of energy, focus, fatigue, and alertness. Pre- to postseason comparisons were made between starters (28.3 ± 5.2 minutes per game) and nonstarters (NSs) (8.3 ± 5.3 minutes per game). Data were analyzed for clinical significance using an approach based on the magnitude of change. Results revealed that starters were likely to have greater increases in absolute VJ peak power and relative VJ peak power (87.9 and 90.7%, respectively) and they were likely (81.6%) to have a greater average squat power than NSs. Subjective measures of energy, focus, and alertness were possibly (72.9%), very likely (97.3%), and likely (79.2%) to be lower in starters compared with NSs, respectively. Other performance measures showed unclear differences between starters and NSs. Pearson`s product-moment correlation analysis revealed significant (p < 0.05) inverse correlations between playing time and d focus (r = -0.79) among all players. In conclusion, significant improvements in VJ performance and average squat power were seen in starters compared with NSs, despite greater decreases in energy, focus, and alertness. In this study, the monitoring of sport-specific performance changes pre and post season showed that performance measures can be maintained throughout an National Collegiate Athletic Association Division I women basketball season.